2002
DOI: 10.1046/j.1365-2516.2002.00671.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost related to replacement therapy during hospitalization in haemophiliacs with or without inhibitors: experience of six French haemophilia centres

Abstract: Replacement therapy in haemophiliacs has a major economic impact on health establishments. We assessed in this prospective study the cost of clotting factor concentrate therapy for haemophilia A or B patients. We compared the overall costs of treated patients with or without inhibitors. In six French haemophilia centres, 278 consecutive hospitalizations were collected and analysed between June 97 and June 99. Haemophilia must be considered as the main cost factor during hospitalization. The severity of bleeds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 5 publications
2
16
2
Order By: Relevance
“…The median daily hospitalization costs in patients who did or did not undergo surgical procedures were 2.4- and 5.6-fold higher, respectively, in patients with high-responding inhibitors. Gautier, et al22 reported that the daily cost was 2-5-fold higher in French patients with HA and high-responding inhibitors during hospitalization. Costs related to bypassing agents accounted for more than 90% of the total inpatient costs related to CFCs among patients with high-responding inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…The median daily hospitalization costs in patients who did or did not undergo surgical procedures were 2.4- and 5.6-fold higher, respectively, in patients with high-responding inhibitors. Gautier, et al22 reported that the daily cost was 2-5-fold higher in French patients with HA and high-responding inhibitors during hospitalization. Costs related to bypassing agents accounted for more than 90% of the total inpatient costs related to CFCs among patients with high-responding inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Both France and Italy found the total cost of treating patients in the prophylaxis group was significantly higher (around 3.5 times, 3.7-4.1 times for direct costs) than in the OD group, while in Germany prophylaxis group costs were lower than the OD group. Hospitalisation costs were highest in the French OD group (64% of direct There appears to be no significant variation in hospitalisation costs between type A and B haemophilia (91), but annual treatment costs may vary with age, as German evidence shows paediatric patients, both with and without inhibitors, cost much less to treat than adults (by more than 4 times in both groups) (92).…”
Section: Schramm Et Al Examined Costs Incurred By Patients In Both Pmentioning
confidence: 94%
“…Although this threshold is used in most French studies, it differs from the factor levels of less than 1% used in other international studies to define severe haemophilia [4,[7][8][9][11][12][13][14]. We also defined the presence of a circulating inhibitor to the coagulation factors when the titre of the inhibitor was C0.8 BU, repeated twice.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with inhibitors were classified as either high responders with an inhibitor titre of[5 BU or low responders with an inhibitor titre of \5 BU. This threshold is generally admitted by most authors [6,8,[11][12]. However Goudemand et al set a threshold at 10 BU and Molho et al defined the presence of an inhibitor with a titre of [0.6 BU [4,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation